Generation of Doubled Haploid Wheat-Triticum urartu Introgression Lines and Their Characterisation Using Chromosome-Specific KASP Markers - Grewal, Surbhi; Guwela, Veronica; Newell, Claire; Yang, Cai-yun; Ashling, Stephen; Scholefield, Duncan; Hubbart-Edwards, Stella; Burridge, Amanda; Stride, Alex; King, Ian P.; King, Julie (Frontiers in Plant Science, 2021)
Wheat is one of the most important food and protein sources in the world and although, in recent years wheat breeders have achieved yield gains, they are not sufficient to meet the demands of an ever-growing population. Development of high yielding wheat varieties, resilient to abiotic and biotic stress resulting from climate change, has been limited by wheat’s narrow genetic base. In contrast to wheat, the wild relatives of wheat provide a vast reservoir of genetic variation for most, if not all, agronomic traits. Previous studies by the authors have shown the transfer of genetic variation from T. urartu into bread wheat. However, before the introgression lines can be exploited for trait analysis, they are required to have stable transmission of the introgressions to the next generation. In this work, we describe the generation of 86 doubled haploid (DH) wheat-T. urartu introgression lines that carry homozygous introgressions which are stably inherited. The DH lines were characterised using the Axiom® Wheat Relative Genotyping Array and 151 KASP markers to identify 65 unique T. urartu introgressions in a bread wheat background. Doubled haploid production has helped accelerate the breeding process and facilitated the early release of homozygous wheat-T. urartu introgression lines. Together with the KASP markers, this valuable resource could greatly advance identification of beneficial alleles that can be used in wheat improvement.